Ketepatan Penerjemahan Konjungsi Koordinatif Bahasa Inggris dalam Novel Animal Farm Versi Bahasa Indonesia - Rumbardi, Rumbardi; Khoiriyah, Atifah (Linguistika Kultura, 2024)
This study examines the accuracy of translating English coordinating conjunctions into Indonesian in the novel Animal Farm. The aim of the research is to analyze the translation techniques used for these conjunctions and evaluate the accuracy of the English sentences containing them. A qualitative approach is employed, with data drawn from the English version of Animal Farm and its Indonesian translation, Republik Hewan. The researcher uses Newmark’s theory to identify the translation procedures and Nababan’s theory to assess translation accuracy. The results indicate that 78% of the data are translated using a literal procedure, while 22% employ a reduction translation procedure. In terms of accuracy, 57% of the data are considered accurate, 13% less accurate, and 8% inaccurate. The accuracy level appears to be influenced by the translation of coordinating conjunctions as well as other sentence components.